Health and Rights at the Margins: Human trafficking and HIV/AIDS amongst Jingpo ethnic communities in Ruili City, China - Shih, Elena (Anti-Trafficking Review, 2013)
In 2007, China and Myanmar signed their first Bilateral Memorandum of Understanding on human trafficking. The two countries cemented this agreement with the unveiling of the first Border Liaison Office in Ruili City, located in China’s southwestern Yunnan Province — one of the primary border crossing points between China and Myanmar. The government focus on human trafficking on this border intersects with decades of struggles to curb the border’s porousness to drugs and HIV/AIDS. This paper is based on qualitative ethnographic participant observation and interviews with young Jingpo women living in Ruili City and investigates the risk of human trafficking as a by-product of cultural stigma associated with ethnic marginality, drugs, and HIV/AIDS. The case of Ruili warns us that the global shift towards regarding human trafficking as the single most perilous phenomenon of the current age obscures ongoing issues of vulnerability and cultural stigma for ethnic minority peoples globally. In lieu of state sponsored patrol and monitoring of the border, more attention must be paid to overlapping concerns of people living in border communities, including drug prevalence, disease, and ethnic marginalisation.